Drivers of poor medical care. Issue 10090 (8th July 2017) - Saini, Vikas; Garcia-Armesto, Sandra; Klemperer, David; Paris, Valerie; Elshaug, Adam G; Brownlee, Shannon; Ioannidis, John P A; Fisher, Elliott S
Summary: The global ubiquity of overuse and underuse of health-care resources and the gravity of resulting harms necessitate an investigation of drivers to inform potential solutions. We describe the network of influences that contribute to poor care and suggest that it is driven by factors that fall into three domains: money and finance; knowledge, bias, and uncertainty; and power and human relationships. In each domain the drivers operate at the global, national, regional, and individual level, and are modulated by the specific contexts within which they act. We discuss in detail drivers of poor care in each domain.